Numerical Simulation Study on the Influence of Different Factors on the Uplift Bearing Capacity of Root Piles, Straight-Shaft Piles, and Pedestal Piles - Junpeng Zhou; Jun Yuan; Xuefeng Huang; Xueming Wang (Advances in Civil Engineering)
Root pile (hereafter called RP), which is a promising new type of noncircular cross-section-shaped pile and meets the requirements of the development of the uplift pile, was introduced for promotion. On the basis of validation of experimental and numerical results, finite element models were established to study the influence of the arrangement of roots and dimension parameters on the uplift bearing capacity and the economy of RP compared with that of the straight-shaft pile and pedestal pile (hereafter called SP and PP, respectively). The results show that the uplift bearing capacity of RP is higher than that of SP and PP, and the longer the pile length is, the more the bearing capacity of RP would increase compared with that of SP and PP. In order to further improve the bearing capacity of RP, the bearing mechanism of the root was analysed, and the suggested values of root size and spacing of layers are given. In addition, the most economical way to increase pile bearing capacity is to increase pile length rather than increasing pile diameter.